Utilizing liposomal encapsulation approach to address nephrotoxic challenges of colistimethate sodium through a preclinical study - Raktham Mektrirat; Noppanut Paengjun; Peerawit Chongrattanameteekul; Sonthaya Umsumarng; Suppara Cheunsri; Kornravee Photichai; Kittima Lewchalermvong; Chalutwan Sansamur; Siriporn Okonogi; Wasan Katip (Frontiers in Pharmacology, 2023)
cells/mL). Our study findings enhance the understanding of the safety profile of CL and its potential to improve patient outcomes through the use of liposomal colistin medication. Additional clinical studies are necessary to establish the optimal safety regiment in humans.
Keywords: Antibiotic Resistance in Bacteria; Urinary Tract Infections Management; Antibiotics Pharmacokinetics and Efficacy